Pathological and molecular investigation of infectious bronchitis in broilers: analyzing the impact of biosecurity lapses - Maletić, Jelena; Jezdimirović, Nemanja; Spalević, Ljiljana; Milovanović, Bojan; Vasić, Ana; Kureljušić, Jasna; Kureljušić, Branislav (Frontiers in Veterinary Science, 2025)
IntroductionInfectious Bronchitis (IB) is an acute, highly contagious disease of poultry that leads to significant economic losses in intensive production systems. Preventive biosecurity measures are essential to control its spread, particularly in broiler farms. This study aimed to investigate the relationship between IB outbreaks and biosecurity practices on a broiler farm.MethodsThe farm, housing 96,000 broilers, experienced increased mortality (over 11%) during two consecutive production cycles. Consequently, serological, pathological, molecular and biosecurity investigations were conducted.ResultsDespite a vaccination program using two types of live vaccines (Massachusetts serotype and serotype 793B), serological testing revealed elevated antibody titers against the IB virus, suggesting exposure to a wild viral strain. Necropsy revealed various lesions, including hemorrhagic tracheitis, pulmonary hyperemia, fibrinous pericarditis, splenomegaly, and ascites. Histopathological findings showed necrotic tracheitis, multifocal hepatitis, and purulent bronchopneumonia. By PCR IB viral RNA was detected in all 24 swabs and tissue samples. Biosecurity evaluation revealed significant deficiencies in both external and internal measures, including improper cross-contamination prevention, inadequate flock management, and insufficient vaccination strategies.DiscussionThese biosecurity deficiencies, coupled with the inadequate selection of vaccines not tailored to the prevalent serotypes in the local area, allowed for the introduction and spread of wild IB virus strains. This highlights the critical importance of robust, well-implemented biosecurity protocols in preventing IB on poultry farms.